The role of mothers and fathers in providing skills: Evidence from parental deaths - Jérôme Adda; Anders Björklund; Helena Holmlund (Institute for the Study of Labor (IZA), 2011)
This paper evaluates the long-term consequences of parental death on children's cognitive and noncognitive skills, as well as on labor market outcomes. We exploit a large administrative data set covering many Swedish cohorts. We develop new estimation methods to tackle the potential endogeneity of death at an early age, based on the idea that the amount of endogeneity is constant or decreasing during childhood. Our method also allows us to identify a set of death causes that are conditionally exogenous. We find that the loss of either a father or a mother on boys' earnings is no higher than 6-7 percent and slightly lower for girls. Our examination of the impact on cognitive skills (IQ and educational attainment) and on noncognitive skills (emotional stability, social skills) shows rather small effects on each type of skill. We find that both mothers and fathers are important, but mothers are somewhat more important for cognitive skills and fathers for noncognitive ones.
urn:nbn:de:101:1-201104084364
Keywords: J12; J17; J24; 330; family background; cognitive and noncognitive skills; parental death; Kinder; Kognitive Fähigkeiten; Emotion; Eltern; Sterblichkeit; Familiensoziologie; Schweden